2017
DOI: 10.19086/da.1245
|View full text |Cite
|
Sign up to set email alerts
|

On cap sets and the group-theoretic approach to matrix multiplication

Abstract: In 2003, Cohn and Umans described a framework for proving upper bounds on the exponent ω of matrix multiplication by reducing matrix multiplication to group algebra multiplication, and in 2005 Cohn, Kleinberg, Szegedy, and Umans proposed specific conjectures for how to obtain ω = 2. In this paper we rule out obtaining ω = 2 in this framework from abelian groups of bounded exponent. To do this we bound the size of tricolored sum-free sets in such groups, extending the breakthrough results of Croot, Lev, Pach, E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(146 citation statements)
references
References 27 publications
7
139
0
Order By: Relevance
“…Sets that contain no arithmetic progressions have also been studied over other abelian groups, see [6] and [20]. We expect these methods can be used in those settings as well to improve bounds on the corresponding removal lemma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sets that contain no arithmetic progressions have also been studied over other abelian groups, see [6] and [20]. We expect these methods can be used in those settings as well to improve bounds on the corresponding removal lemma.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we have 1 c 2 = 5/3 − log 3 ≈ .0817 and [9] showed that their method can be used to greatly improve the upper bound on the cap set problem, and more generally to bound the size of a set in F n p with no 3-term arithmetic progressions. Further work by Blasiak-Church-Cohn-Grochow-NaslundSawin-Umans [6], and independently Alon, established that their proof also shows the following multicolored sum-free theorem over F n p . Later work by Kleinberg, Sawin, and Speyer [16] showed that there exists a computable exponent c p that is sharp.…”
Section: Introductionmentioning
confidence: 93%
“…After Blasiak et al . established the upper bound, Kleinberg, Sawin, and Speyer proved Theorem for k=3 and any m2. Their proof uses a statement that had been formulated as a conjecture in an earlier version of their paper and was then proved by Pebody .…”
Section: Introductionmentioning
confidence: 97%
“…Soon after the preprint of Ellenberg and Gijswijt appeared, Blasiak, Church, Cohn, Grochow, Naslund, Sawin, and Umans and independently Alon noticed that the argument of Ellenberg and Gijswijt can also be used to obtain an upper bound on the size of k‐colored sum‐free sets in Fpn with k=3 (see the following definition). Definition Let G be an abelian group and let k3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation